Russian Classics on Screen: In Search of Artistic Meaning (Leskov’s Katerina Ismailova in Balayan’s Film Adaptation) - Ситникова, Вера (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2014)
The paper tackles the problem of trivialization in a screen adaptation, taking as an example Nikolai Leskov’s sketch ‘The Lady Macbeth of Mtsensk’ and Roman Balayan’s 1989 film based on it. The author focuses on biblical contexts and contrasts the tone of the ending in the text with that on screen: while the literary Katerina remains unable to repent and ready to murder, the scenery toward the end of the film is surprisingly serene. In particular, the director’s treatment of the motif of ringing bells (symbolizing man’s separation from God) reveals an ideological difference between Balayan and Leskov. The author finds Balayan’s version more of a love drama than a tragedy of the death of a human soul. The film, she claims, even if not essentially distorting the meaning of the sketch, downplays and impoverishes Leskov’s semantic palette and simplifies the complex character created by the writer.